Listening to Laredo : A Border City in a Globalized Age - Momen, Mehnaaz (Book collections on Project MUSE., 2023)
"Nestled between Texas and Mexico, the city of Laredo was a conventional border town, nurturing cultural ties across the border, attracting occasional tourists, and populated with people living there for generations. This book examines the existing economic and cultural infrastructure of the city, its interdependence with its sister city across the national boundary, and, most importantly, the resilience of the community to adapt to and even challenge the national narrative on the border"--